(3GdJhLjg aj TQM GdeZfj eNJUQ GdJfHjgs - (3HQgGf GdOjf CHi ESMGb EHQGgje Hf CjhH GdGjfGSis; (3GHf GdHGQRj , gHI Gddg Hf YHO GdQMje Hf EHQGgje, TQa GdOjf CHhGdbGSe,J (B738 (3g` s
(3ChdgG (B:s
(3HcJGH GdfcGM s
(3BNQgG (B:s
(3abg GdCbGQH s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B73 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B139s
Keywords: (3Gdabg GdTGaYjs